2014
DOI: 10.1037/a0035775
|View full text |Cite
|
Sign up to set email alerts
|

Enabling possibility: Women associate professors’ sense of agency in career advancement.

Abstract: In this multimethod, qualitative study we examined associate women professors' sense of agency in career advancement from the rank of associate to full. Defining agency as strategic perspectives or actions toward goals that matter to the professor, we explore the perceptions of what helps and/or hinders a sense of agency in career advancement. Our participants consisted of 16 women associate professors at a major research university who participated in an institutional intervention program designed to enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 696 publications
5
82
0
1
Order By: Relevance
“…In line with related past research, the findings revealed that their engagement in volunteer work supported their career development (Tight, 2002;Ismail, 2005;Newmann et al, 2006;Ismail et al, 2011;Safiah et al, 2012;Terosky et al, 2014). The findings also resonate with studies showing that religious belief is an important factor influencing people's engagement in volunteerism, and the role of religious belief in promoting altruism (Hunter & Linn, 1980;Wuthnow, 1999;Greeley, 1997;Mattis, Jagers, Hatcher, Lawhon, Murphy & Murray, 2000;Lam, 2002).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In line with related past research, the findings revealed that their engagement in volunteer work supported their career development (Tight, 2002;Ismail, 2005;Newmann et al, 2006;Ismail et al, 2011;Safiah et al, 2012;Terosky et al, 2014). The findings also resonate with studies showing that religious belief is an important factor influencing people's engagement in volunteerism, and the role of religious belief in promoting altruism (Hunter & Linn, 1980;Wuthnow, 1999;Greeley, 1997;Mattis, Jagers, Hatcher, Lawhon, Murphy & Murray, 2000;Lam, 2002).…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, the enthusiasm to serve others must be sustained over time. Sustaining an academic career requires not only a determined commitment of time and energy into appropriate activities, but also demands access to appropriate resources and institutional assistance that facilitates career feasibility (Ismail, 2005;Crepeau, Thibodaux & Parham, 1999;Terosky et al, 2014). This determined commitment of time is a function of career development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations